Robin Hood - "Bull, Angela" (Great Britain china, 2000)
Recounts the life and adventures of Robin Hood, who, with his band of followers, lived as an outlaw in Sherwood Forest dedicated to fighting tyranny. Illustrated notes throughout the text explain the historical background of the story
Keywords: Children's fiction